Effects of stevia on glycemic and lipid profile of type 2 diabetic patients: A randomized controlled trial - Marjan Ajami; Maryam Seyfi; Fatemeh Abdollah Pouri Hosseini; Parisa Naseri; Aynaz Velayati; Fahimeh Mahmoudnia; Maliheh Zahedirad; Majid Hajifaraji (Mashhad University of Medical Sciences, 2020)
Objective: Stevia (Stevia rebaudiana Bertoni) is a natural and healthyalternative sweetener to sugar and artificial sweeteners, which has become important for human diets and food manufactures. In this study, the effects of stevia or sucralose as tea sweeteners on glycemic and lipid profile of type 2 diabetic patients were investigated. Materials and Methods: A double-blind clinical trial was carried out in 34 type 2 diabetic patients. These patients were assigned into two groups of stevia (n=15) (received 1 cup of 2% stevia extract-sweet tea in three meals) and non-stevia (n=19) (received one tablet of sucralose sweetener) daily for eight weeks. Glycemic response and lipid profile of the participants were assessed. Furthermore, height, weight and body mass index (BMI) of the participants were measured as well as their dietary intakes at the baseline and at the end of the study. Results: Findings showed no significant differences in fasting blood sugar (FBS) levels between the base line and after two hours, in participants. Also, no significant differences in insulin, glycosylated hemoglobin (HbA1C) and lipid levels were found between the two groups. Conclusion: Results of the current study showed that the highlighted doses of stevia in sweetened tea could be an alternative to sucralose in diabetic patients with no effects on blood glucose, HbA1C, insulin and lipid levels.